An effective polyvinyl alcohol for the solubilization of poorly water-soluble drugs in solid dispersion formulations - Umemoto, Yoshiaki; Uchida, Shinya; Yoshida, Takatsune; Shimada, Ken; Kojima, Hiroyuki; Takagi, Akira; Tanaka, Shimako; Kashiwagura, Yasuharu; Namiki, Noriyuki (Journal of drug delivery science and technology, 2020)
This study aimed to investigate the characteristics of an effective polyvinyl alcohol (PVA) for use in solid dispersion formulations (SDFs), which enable higher dissolution and bioavailability of poorly water-soluble drugs. PVAs with different degrees of hydrolysis and polymerization were evaluated using their SDFs with amenamevir prepared by ball milling. The dissolution tests suggested that a lower degree of polymerization (≤600) was preferable and that a 66% degree of hydrolysis (PVA 66) was optimal for solubilizing amenamevir. The versatility of the most effective PVA as revealed in the amenamevir dissolution tests was also confirmed using SDFs with nifedipine and tacrolimus prepared by spray-drying. In addition, to investigate the cause for the difference in solubilizing ability by different degrees of hydrolysis, critical micelle concentrations of PVAs were evaluated using pyrene. This suggested that a surfactant ability could be one of the causes. Furthermore, in vivo absorption studies on amenamevir SDFs were conducted by oral administration to rats. PVA 66 achieved higher bioavailability and more rapid absorption than common SDF carriers, such as hydroxypropylmethylcellulose and hydroxypropylmethylcellulose acetate succinate. Thus, PVA with an approximately 66% degree of hydrolysis was beneficial for the solubilization of poorly water-soluble drugs in SDFs. [Display omitted]